Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/ani12213032
|View full text |Cite
|
Sign up to set email alerts
|

Wildlife Disease Monitoring: Methods and Perspectives

Abstract: In the last few decades, scientific interest in wildlife diseases has steadily grown and has recently been boosted by the SARS-CoV-2 pandemic, which highlighted that the health of humans, livestock, wildlife and, ultimately, of the whole environment is inextricably linked [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Current wildlife health surveillance schemes present major flaws (Ryser-Degiorgis, 2013;OIE, 2019;Lawson et al, 2021;Machalaba et al, 2021;Giacinti et al, 2022;Mazzamuto et al, 2022;Delgado et al, 2023;Pruvot et al, 2023) and have not been able to forecast and prevent the onset of new epidemics jumping interspecific barriers and even becoming pandemics (Konda et al, 2020;Delahay et al, 2021;Sharun et al, 2021;Keusch et al, 2022). The combination of WHM and HCM to achieve effective IWM has the potential to overcome these limitations, but it also faces new A modeling study including both host community (HCM) and wildlife health monitoring (WHM) variables obtained from literature review and publicly available databases not only identified the host species of Rift Valley fever virus, but also allowed to disentangle the factors driving a wildlife species to be such a host.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Current wildlife health surveillance schemes present major flaws (Ryser-Degiorgis, 2013;OIE, 2019;Lawson et al, 2021;Machalaba et al, 2021;Giacinti et al, 2022;Mazzamuto et al, 2022;Delgado et al, 2023;Pruvot et al, 2023) and have not been able to forecast and prevent the onset of new epidemics jumping interspecific barriers and even becoming pandemics (Konda et al, 2020;Delahay et al, 2021;Sharun et al, 2021;Keusch et al, 2022). The combination of WHM and HCM to achieve effective IWM has the potential to overcome these limitations, but it also faces new A modeling study including both host community (HCM) and wildlife health monitoring (WHM) variables obtained from literature review and publicly available databases not only identified the host species of Rift Valley fever virus, but also allowed to disentangle the factors driving a wildlife species to be such a host.…”
Section: Discussionmentioning
confidence: 99%
“…Establishing, developing, and implementing wildlife health surveillance programs is a worldwide priority and a challenge within the One Health approach (Ryser-Degiorgis, 2013;OIE, 2019;Lawson et al, 2021;Machalaba et al, 2021;Giacinti et al, 2022;Mazzamuto et al, 2022;Delgado et al, 2023;Pruvot et al, 2023). Traditionally, wildlife health surveillance is considered to encompass general surveillance (also called scanning or passive surveillance) and targeted surveillance (formerly called active surveillance) (Ryser-Degiorgis, 2013;OIE, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obtaining data by sampling wild birds could seem difficult, as it requires considerable logistical efforts, but this is not completely true. Bird ringing camps and wild animal rescue centers (only if sampling is carried out at arrival) are fundamental components of epidemiological surveillance work (Mazzamuto et al 2022). There are easy, economic, atraumatic, and non‐invasive methods for sampling birds without interfering in their welfare, both in wildlife rescue centers and in bird ringing camps.…”
Section: A Wild Bird Monitoring Approach For Amr Surveillancementioning
confidence: 99%
“…While there are entire books, guidelines, and journal issues written on methods for sample collection in wild birds for infectious diseases (Martin et al, 2006;Mazzamuto et al, 2022), there remains no standardization for samples collected from wild birds or the environment near wild bird populations. The most common samples collected in live wild birds are cloacal and tracheal or oropharyngeal swabs, and blood for serology, immunology, and overall health.…”
Section: Sample Collection Techniquesmentioning
confidence: 99%